Urban Development and Regeneration in Ancoats, Manchester: From Industrial Suburb to Urban Village - Aurore Caignet (Angles)
Located on the north eastern edge of Manchester city centre, Ancoats was the first industrial suburb in the world when early steam-powered mills were built in the late Eighteenth Century. After it was severely hit by industrial decline over the course of the Twentieth century and its industrial buildings fell into disrepair, this area benefitted from a regeneration process which was implemented in the 1990s. It relied on the conservation and conversion of historic buildings and was influenced by the urban village model. This paper explores the mutation of an urban quarter born out of a pioneering experiment in industry-led urban development which was to become an urban village two centuries later. However, the urban village concept was an idealised vision of regeneration that was not fully compatible with the industrial character of Ancoats. The Ancoats Urban Village Company thus developed a different urban design approach, thereby carrying out an urban regeneration experiment of its own which reflects both change and continuity.